Notas sobre Naucoroidea (Hemiptera: Naucoridae). 3ra. Serie. Estudios con microscopio electrónico de barrido: corion de los huevos de Ambrysus (Ambrysus) attenuatus Montandon, Ambrysus (Ambrysus) acutangulus Montandon y Ambrysus(Ambrysus) stali La Rivers (Lundiana: International Journal of Biodiversity, 2007)
Chorionic sculpturing differs interespecifically in Ambrysus Stål. The eggs of three species were examined with scanning electron microscopy, described and illustrated. Different patterns on the chorion were found in the three species. In A. acutangulus and A. stali, a rounded area with different pattern appears at the anterior pole and the design disappears near the micropyla. In A. attenuatus the pattern is uniform on the surface.